Europe's under-the-radar industrial policy: Intervention in electricity pricing - Ben McWilliams; Giovanni Sgaravatti; Simone Tagliapietra; Georg Zachmann (Bruegel, 2024)
The different ways in which European Union member-state governments add levies to the price of electricity creates huge discrepancies in the prices paid by consumers. Europe's energy transition depends upon increasing electrification of the economy and increasing the share of that electricity produced by renewable sources. Both factors raise the importance of electricity taxes set by governments. The energy crisis drew attention to this: as electricity prices soared, governments responded with billions of euros in subsidies to protect households and companies. While the acute phase of the energy crisis has passed, growing concerns about industrial competitiveness create political pressure for governments to continue with such subsidies or tax exemptions. High profile examples include the French reform of nuclear-power generated electricity pricing, and a political debate in Germany over how aggressively to subsidise the electricity price paid by energy-intensive firms. We frame the debate on intervention in electricity pricing around five distributional dilemmas concerning the recuperation of electricity expenses: 1) whether to raise general or electricity taxes, 2) the split between household and companies, 3) the split between energyintensive and non-energy intensive companies, 4) cross-border effects, and 5) trade-offs in attracting new clean-technology manufacturing factories. Priorities according to these distributional criteria will differ by country, but these factors should be central to discussions. Governments must recognise that efforts to lower prices artificially for one group of consumers will raise prices for others, including with crossborder implications. The current compromises in the French and German cases do not pose substantial issues to the integrity of the European single market and do not penalise nonenergy-intensive domestic consumers excessively.
Keywords: 330